Survey of Fusarium species on yellow onion (Allium cepa) on Öland - Lager, Sara (SLU/Dept. of Forest Mycology and Plant Pathology, 2011)
It has been observed by both onion producers and a plant protection advisor on Öland (an island off the east coast of Sweden) that basal rot is the largest contributory factor to reduced onion quality and yield. Basal rot is mainly caused by species of Fusarium fungi. The aim of this study was to: a) investigate which species of Fusarium that can be found in onion produced on Öland, b) describe the symptoms caused by the different Fusarium fungi found and c) explore, through interviews with the onion producers on Öland, the mechanisms that may be involved in the observed increase in basal rot.